Pengaruh Urgensi Sosialisasi Perpajakan Terhadap Wajib Pajak Dalam Mendukung Kepatuhan Membayar Pajak Di Kantor Pelayanan Pajak Pratama Makassar Selatan - Andi Indah Lestari AM; Wiwi Diayanti (YUME : Journal of Management, 2021)
The purpose of this study was to determine the urgency of tax socialization to taxpayers in supporting compliance in paying taxes at KPP Pratama South Makassar and to determine the magnitude of the effect of the urgency of tax socialization on taxpayers in supporting compliance with paying taxes at KPP Pratama South Makassar. This type of research uses quantitative methods with data collection techniques through questionnaires, documentation, and observations where the questionnaires in this study are distributed to individual taxpayers using the non-probability sampling-quota sampling method with purposive sampling. multiple linear regression, hypothesis testing with partial test, and simultaneous test.The results of this study indicate that the urgency of taxation socialization, knowledge of taxation, awareness of taxpayers towards tax compliance has an effect of 61.9% as seen from the results of the coefficient of determination (R2). Based on the hypothesis test using t test where t count > t table 1.294. And F count 35,725 > F table 2,744 with a significant value of 0.000 < 0.05, then the hypothesis states that Ha is accepted and Ho is rejected. This shows that there is a significant effect.Universitas Internasional BatamKeywords: Urgency of Tax Socialization, Taxpayers, Compliance with paying taxes